Evaluation of Limnological Status of Jagadishpur Reservoir, Kapilvastu District, Nepal - Chaudahary, R.K.; Devkota, A. (International Journal of Applied Sciences and Biotechnology, 2018)
The aim of this research was to analyze physical and chemical characteristics of low altitude lake of Jagadishpur Reservoir, a Ramsar site in central Nepal lies about 197 m altitude. The reservoir water was studied for three seasons (rainy, winter and summer) to compare the changes in the parameters. Water quality in reservoir was found less favorable to aquatic organisms, with low pH and transparency, low dissolved oxygen (DO), and high nutrient concentrations (Nitrogen). The reservoir was found eutrophic in nature by nitrogen concentration and transparency criteria. The findings created a database for present status of low land water reservoir of Nepal, which can be used for the management of lakes as well as to study the impact on water quality.This study provided useful information for decision makers aimed to the conservation and sustainable management of the reservoir. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 255-260